Al-Istisyfâi bi Al-‘Asl fi Al-Qur’an ‘Inda Zaghlul Râghib Al-Najjâr - Sujiat Zubaidi Shaleh; Intan Pratiwi Mustikasari (Studia Quranika, 2018)
This article aims to describe the views of Zaghloul Raghib Muhammad an-Najjar on the meaning of treatment with honey in the Qur'an and the meaning of honey in the Qur'an. As a mufaseer and scientist, an-Najjar was able to explain the ' ilmy i'jaz al-Qur'an in the related to verses kauniyyah scientifically by presenting scientific evidence that is in line with the development and progress of science knowledge. In this study, the researchers applied the method of analysis and descriptive text-analysis to elucidate the main reference Tafseer Kauniyah which deals with the problems above. The result of this research concludes that Zaghloul an-Najjar in his tafseer confirms the meaning of syarâb in the surah an-Nahl. He mentioned the characteristics of honey bees in the verse as liquid substances with different color that came out from the body of a bee which is effective as a cure for humans.